Dental technology of Taiwan during the Japanese colonial period - Feng-Chou Cheng; Ling-Hsia Wang; Natsuyo Ozawa; Chen-Ying Wang; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2022)
Background/purpose: During the Japanese colonial period, the Taipei Hospital had already provided complete dental services with a fixed price per treatment. This study tried to compare the differences in the prices of various dental treatments between the Japanese colonial period and today. Materials and methods: This study used the "Dental Treatment Fees in the 27th Annual Report of Taipei Hospital (Taisho 12)" as the study materials to compare the differences in the prices of various dental treatments between the Japanese colonial period and today using the monthly salary of a novice elementary school teacher as an income benchmark. Results: A hundred years ago, the Taipei Hospital had already provided the dental treatments such as scaling and endodontic, operative dentistry, prosthodontic, and orthodontic treatments. Of these treatment items, the prices for prosthodontic and orthodontic treatments were more expensive. After a century of development, the costs of scaling and operative dentistry treatments dropped, while the costs of endodontic, prosthodontic, and orthodontic treatments increased. Conclusion: During the Japanese colonial period, Taiwan's dental treatment technology had already had the forms of modern dentistry with several dental specialties. At that time, the costs of dental treatments are quite expensive. Today's dental treatment items are more detailed and diverse. The health insurance system provides Taiwanese people with convenient and cheap general dental treatments such as scaling and treatments related to operative dentistry, endodontics, periodontics, and oral surgery. However, the costs of prosthodontic and orthodontic treatments increase and have to be paid by the patients themselves.